Detection of Tuberculosis Infection by Interferon Gamma Release Assay (IGRA) in Healthcare Workers of Regional Health 10 during 2019-2020 - คำแสน, จันทร์ฉาย (Journal of Health Science of Thailand, 2022)
This study aimed to detect M. tuberculosis by interferon gamma release assay (IGRA) in health personnel of Public Health Region 10 as a supportive measure to prevent and control tuberculosis. It was conducted during 2019-2020. The samples were 439 personnel from 20 hospitals in the Public Health Region 10: 100 men and 339 women aged 23-61 years old. The health personnel were from 1 regional hospital, 2 general hospitals and 17 community hospitals in the 4 provinces: Ubon Ratchathani (10), Amnat Charoen (7), Sisaket (2) and Mukdahan (1) with 353, 43, 37 and 6 persons, respectively. There were 62 tuberculosis positive cases (14.12%). By province, the positive results were 46 cases (13.03%), 6 cases (13.95%), 9 cases (24.32%), and 1 case (16.67%), respectively. The positive cases were from different professional groups: 3 positive cases among 20 persons from physician group (15.00 %), 2 positive cases from 10 person in dental group (20.00%), 2 from 11 in pharmaceutical group (18.18%), 10 from 111 in medical technology group (9.01%), 33 from 229 in nursing group (14.41%), and 3 from 12 in X-rays technician group (25.00%). Categorized by clinical group, there were 8 positive cases among 24 persons of TB clinic and disease control group (33.33%), and 1 of 17 in administrative group (5.88%). From this study, it was found that healthcare workers were at higher risk for acquiring M. tuberculosis, especially those who were in close contact with patients. Therefore, medical facilities should have measures to prevent medical and health personnel from tuberculosis by promoting, preventing and providing care in order to maintain good health and continue to be important manpower of the country’s public health system.